Manajemen Pembinaan Peserta Didik Dalam Meningkatkan Motivasi Belajar - Hasanah, Nurul; Rizkianti, Sofiatur; Khoiri, Ahmad; Ulum, Nuzzulul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This article further delineates the implementation of student development management through both curricular and extracurricular activity programs. The research employs a qualitative approach, specifically case study research focused on fieldwork. The study centers on the following aspects: First, the role of school principals in designing student development programs aimed at enhancing learning motivation. Second, the execution of student development programs with the objective of increasing learning motivation. Third, the oversight of the student development program by the principal. Fourth, the evaluation conducted by the principal to identify obstacles and successes within the implemented program. Keywords: Coaching Management; Learning Motivation.